The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7874/jao.2017.00164
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Pattern of Published Articles in the Field of Otology: 1818 to Today

Abstract: To examine and identify the changing pattern of published articles in the otology literature over the past several decades. We used a variety of search engines available through PubMed.gov based on key words in the following categories: diagnosis, diagnostic tools, and therapeutic tools. The number of searchable key words increased from 1945 to the present. Overall, there has been a major shift in topics cover in the otological literature. Most recently, there has been significant increases in the following ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…With an increasing academic requirement, there is a need to assess the multifaceted research progress in dyslexia. There has been some bibliometric studies reported in speech, language and hearing sciences, public health 17 , ophthalmology 18 , ophthalmic epidemiology and prevention 19 , and otology 20 . None of these studies addresses the research progress associated with dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…With an increasing academic requirement, there is a need to assess the multifaceted research progress in dyslexia. There has been some bibliometric studies reported in speech, language and hearing sciences, public health 17 , ophthalmology 18 , ophthalmic epidemiology and prevention 19 , and otology 20 . None of these studies addresses the research progress associated with dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis published in the field of otology in 2017 indicates that there has been a rapid increase in the total number of articles published in the field of otology in the last few decades, and among these, an increase has been shown in the number of articles related to cochlear implants and hearing aids after the 1990s. 42 Emerging treatment options have popularized the domain of otology and raised the number of papers in otology. Although abrupt growth patterns were related to technological improvements or better yet disruptive technologies, this could not be substantiated in our data.…”
Section: Discussionmentioning
confidence: 99%